MODEL PEMILIHAN NAGENO KATA TERBAIK PADA CABANG OLAHRAGA JUDO DENGAN METODE ANALYTICAL HIERARCHY PROCESS Studi Kasus: Porda Jawa Barat XII Kabupaten Bekasi - Fransiskus Ananda Wibisono; Denny Pribadi (Universitas Bina Sarana Informatika Kota Sukabumi, 2015)
Judo is a part of self defence sport that is popular and become the basic of defend for IndonesianPolice and Indonesian Army members. One of its category is Nagenokata. Nagenokata is the art ofself defence that shows the judo’s techniques. But during the times the judgement to the athletethat follows the competition of Nagenokata in judo’s sport is still manual and subjective so that thewinner choosing in the nagenokata competition is still unprecise. Because of this problem, weneed to make a decision suport system that can make the jury or user of the system easier tochoose the best Nagenokata in judo sport. The method that is going to be used un choosing of thebest Nagenokata is Analytical Hierarchy Process (AHP) and use the tool expert choice in ordermake the data process easier. This method is choosen the best alternative from severalalternatives, in this case the alternative means the athlete based on the certain comparativecriterias with the proponents system hoped that the jury can choose the player that is suitable withthe standard needed.